A Systematic Review and Meta-Analysis of the Role of Sugar-Free Chewing Gum in Dental Caries. (July 2020) - Newton, J.T.; Awojobi, O.; Nasseripour, M.; Warburton, F.; Di Giorgio, S.; Gallagher, J.E.; Banerjee, A.
Objective: To determine the difference in level of dental caries in adults and children who chew sugar-free gum (SFG), compared with those who do not chew SFG or use alternatives such as lozenges, candies, rinses, tablets, and other nonchewing controls. Methods: Systematic review of published literature. Results: Twelve studies of interventions of SFG for dental caries outcomes were included. SFGs were found to significantly reduce caries increment, giving a preventative fraction (PF) of 28% (95% CI, 7% to 48%). Including the 8 trials that used xylitol gum only as the basis of the intervention, the PF was 33% (95% CI, 4% to 61%). No adverse effects were recorded. There was a high level of heterogeneity among the trials included. Conclusion: The findings of this review provide tentative evidence that chewing SFG reduces caries increment in comparison to nonchewing controls. However, there is a considerable degree of variability in the effect and the trials included were generally of moderate quality. There is a need for future research to explore the acceptability and feasibility of the use of SFG as a public health intervention (PROSPERO 2018 CRD42018094676). Knowledge Transfer Statement: The results of this study can be used by clinicians when deciding how best to implement dental caries prevention regimes for their patients. With consideration of cost and patient preference, this information could help to develop national policy directives on caries prevention and dictate the direction of future clinical research.